Protección de derechos de los jueces frente al actuar de las organizaciones criminales en ecuador. - Mejía Ayala, Anderson Leonardo (2025)
This research aimed to measure the perception of judges and Ecuadorian citizens regarding the pertinence of implementing the “Faceless Judges” figure as a mechanism of safety and justice in Ecuador. For this purpose, an introduction was developed that analyzed the influence of criminal organizations in the administration of justice, therefore affecting judicial impartiality and independence. Regarding the methodology, a mixed research approach was used, addressed to comprehend and interpret the meanings and behaviors produced by the object of study. The design was non-experimental, using the survey and interview techniques, in addition to the questionnaire and the guided interview were the instruments. Similarly, a documental analysis was carried out from previous research which led to relevant results. These results allowed to confirm the hypothesis of research about the need to implement the figure of “Faceless judges”, concluding that this figure would guarantee the comprehensive protection of judges